Sarcopenia and quality of life in patients with diabetes mellitus type 2 in a maternal and child center - Guzmán Mallqui, José Luis (Frontiers in Nutrition, 2025)
ObjectiveTo determine the relationship between sarcopenia and quality of life in patients with type 2 diabetes mellitus in a mother and child center, Peru 2024.MethodsThe research was applied, non-experimental, relational, where work was done in 295 diabetic patients. Regarding the technique, observation was used, recording data on a data collection form, and the survey technique was applied, where the SF-36 questionnaire was administered. Grip strength was measured using the Jamar hydraulic dynamometer and the measurement method according to the European Working Group on Sarcopenia in Older People 2 (EWGSOP2).ResultsNormal grip strength was most represented at 57.29%, followed by low grip strength at 42.71% using the EGWSOP criterion. On the other hand, according to the JAMAR method, low grip strength was 61.69%. Regarding quality of life, the average level was obtained (27.12%), high (26.10%), followed by the very high level (18.98%). In addition, a significant correlation was determined between the dimensions of physical function, physical role, bodily pain perception, general health, vitality, social function, emotional role, and mental health of quality of life and sarcopenia (p < 0.001).ConclusionIt is concluded that there was a positive and significant correlation between sarcopenia and quality of life in patients with type 2 diabetes mellitus for both the EGWSOP criterion (r = 0.303) and the JAMAR method (r = 0.306) (p < 0.001).